Traditions and innovations in the manual impacts in recreation and well-being (Research Announcements "Heritage BG", 2025)
In today’s modern world people are getting more and more aware of the power of natural remedies or influences. Our ancestors knew how to use the healing powers of nature and how to apply cure from the nature with simple means. Methods: Traditionally, for generations, these experiences have been passed on and preserved. One of the oldest manual methods of exposure is massage. Results: We studying the effectiveness of the massage skills as manual method or chiropractic for the treatment and prevention of many diseases. Itrestores vital energy and overcomes states of fatigue – the result of stress in modern society, chronic diseases, unhealthy lifestyles and the harmful effects of our environment. The leading symptom of illness and injury is pain. By treating the superficial tissues of the human body, especially the reflex zones, it can affect various organs and tissues, reduce the increased muscle tone arising from pathology and trauma, normalize blood and lymph flow, metabolic processes in tissues and to balance the patient’s psycho-emotional state. Over the past decades, a number of studies have been conducted and the positive effects of massage have been proven. References:Filonov, Sergei. Lechenie na organizma sas sobstveni sili. Sofia, 2015, pp. 228-232.Filipov, Nikolai. Med za zdrave i krasota. Sofia, 1991.Goranova, Zoya, Gergina Markova-Stareishinska, and Leila Kraidjikova. Masaj. NSA, Sofia, 2000.Harnish, Gunther. Lecheben masaj s pchelen med. Aquarius, Sofia, 2001.Kraev, Todor. Lecheben masaj i postizometrichna relaksaciq. Sofia, 2016.Lisovski, Petar. Prochistvane i podmladqvane. Sofia, 2009.Mladenov, Stoimir. Pchelni produkti – hrana i lekarstvo. Sofia, 1989.Topuzov, Ivan. Celulitat – harakteristika i kompleksno lechenie. Sofia, 2000.Avram, Mathew M. "Cellulite: A Review of its Physiology and Treatment." Journal of Cosmetic and Laser Therapy, vol. 6, no. 4, 2004, pp. 181-185, doi:10.1080/14764170410003057.Pinna, Kathryn. Nutrition and Diet Therapy. Wadsworth, 2007.Rossi, Anthony. "A Modern Approach to the Treatment of Cellulite." Dermatologic Clinics, vol. 32, no. 1, 2014, pp. 51-59.Rossi, Ana Beatris R. "Cellulite: A review." Journal of the European Academy of Dermatology and Venereology, vol. 14, no. 4, 2000, pp. 251-262.
Keywords: honey massage; honey; cellulites